2015
DOI: 10.1007/s00044-015-1461-2
|View full text |Cite
|
Sign up to set email alerts
|

Some novel Schiff bases of [1,2,4]triazole bearing haloarene moiety—synthesis and evaluation of antituberculosis properties and neutrophil function test

Abstract: A series of novel Schiff bases of [1,2,4]triazole-bearing haloarene moiety (5a-l) were synthesized from 4-amino-3-methyl-5-mercapto-4H-[1,2,4]triazole (3) and were confirmed by FT-IR, 1 H-NMR, 13 C-NMR, LCMass spectra and elemental analyses and screened for in vitro antituberculosis properties and for neutrophil function test, where they exhibited moderate neutrophil functions and antituberculosis properties. Compounds (5a), (5c), (5f), (5h) and (5i) were moderately sensitive to antituberculosis activity, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 24 publications
0
9
1
Order By: Relevance
“…have reported the design and synthesis of Schiff bases of 1,2,4-triazole-bearing haloarene moiety 173 ( Fig. 37 ) and screened for in vitro anti-TB properties using disc diffusion method (ZOI test) and microplate Alamar Blue assay (MABA) method (MIC test) towards Mtb H 37 Rv strain [ 155 ]. Compounds 173a and 173h having two fluorine atoms at positions 2 and 4 were found to exhibit the highest activity for antituberculosis screening as well as for neutrophil function test.…”
Section: Biological Activities Of 124-triazole Derivativesmentioning
confidence: 99%
“…have reported the design and synthesis of Schiff bases of 1,2,4-triazole-bearing haloarene moiety 173 ( Fig. 37 ) and screened for in vitro anti-TB properties using disc diffusion method (ZOI test) and microplate Alamar Blue assay (MABA) method (MIC test) towards Mtb H 37 Rv strain [ 155 ]. Compounds 173a and 173h having two fluorine atoms at positions 2 and 4 were found to exhibit the highest activity for antituberculosis screening as well as for neutrophil function test.…”
Section: Biological Activities Of 124-triazole Derivativesmentioning
confidence: 99%
“…Infectious diseases are one of the main causes of a large number of deaths [4,11,15]. It is common knowledge that more efficient antimicrobial compounds can be synthesized by combining two or more biologically active heterocyclic systems in a single molecular framework [1,3,8].…”
Section: актуальные вопросы фармацевтической и медицинской науки и прmentioning
confidence: 99%
“…Bioactivity analysis indicated that the compounds have good inhibitory effects on the tested bacteria . Several studies have shown that triazole derivatives have biological activities such as anti‐inflammatory, antibacterial, antifungal, antiviral, anticancer, and antituberculosis . For example, Singh et al developed a series of substituted aryl azide compounds containing o ‐phenylenediamines, which exhibited antifungal activities .…”
Section: Introductionmentioning
confidence: 99%